2011
DOI: 10.1007/s11274-011-0839-7
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal activity of ethanolic extracts of propolis against Staphylococcus aureus isolated from mastitic cows

Abstract: Staphylococcus aureus is an important pathogen for both humans and animals, and it has been an ubiquitous etiological agent of bovine mastitis in dairy farms worldwide. Elimination of S. aureus with classic antibiotics is difficult, and the current study aimed to evaluate the efficacy of ethanolic extracts of propolis (EEP) against S. aureus cultivated in complex media or milk. EEP (0-0.5 mg ml(-1)) decreased growth of S. aureus in BHI media and 1 mg ml(-1) was bactericidal against washed cell suspensions (10(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 33 publications
5
29
0
1
Order By: Relevance
“…However, for the selection of isolates that have a greater chance of being efficient in the process of colonization and growth promotion, the isolates have first to be identified with preliminary in vitro biochemical analysis (Pal et al [2001]; Berg et al [2002]; Bernardes et al [2010]).Taxonomy of selected microorganisms with biotechnological potential in agriculture is thus a key step and, for this reason, sequencing of the 16S rRNA has been successfully used to identify genera such as Bacillus (Porwal et al In [2009], Deepa et al [2010]), Rhizobium, Burkholderia (Ferreira et al [2011]), Enterobacter, Pantoea Serratia , among others (Tian et al [2009]).…”
Section: Introductionmentioning
confidence: 99%
“…However, for the selection of isolates that have a greater chance of being efficient in the process of colonization and growth promotion, the isolates have first to be identified with preliminary in vitro biochemical analysis (Pal et al [2001]; Berg et al [2002]; Bernardes et al [2010]).Taxonomy of selected microorganisms with biotechnological potential in agriculture is thus a key step and, for this reason, sequencing of the 16S rRNA has been successfully used to identify genera such as Bacillus (Porwal et al In [2009], Deepa et al [2010]), Rhizobium, Burkholderia (Ferreira et al [2011]), Enterobacter, Pantoea Serratia , among others (Tian et al [2009]).…”
Section: Introductionmentioning
confidence: 99%
“…The authors noticed that in milk the bactericidal dose was at least 20-fold greater [50]. Interesting results were also published by Suleman and colleagues [51].…”
Section: Bee Products and Essential Oils As Alternative Agents For Trmentioning
confidence: 89%
“…The global market size of propolis was about 2300 tons in 2015 (it is established that it will increase to 2900 tons in 2021), and Brazil is the largest production and exporting country of this product (htps://www.whatech.com/market-research/materials-chemicals/125806-world-propolis-industry-trends-share-size-2021-forecast-report). High anti-staphylococcal activity of propolis sourced from State of Paraná, in Brazil, was observed by PamplonaZomenhan and coworkers, the MIC 50 and MIC 90 for the 210 strains (162 MSSA and 48 MRSA) were both 1420 μg/mL [48]. The results of investigations performed by the groups of Fidoralisi [49] and Santana [50] indicated that propolis extracts might be efective against mastitis-causing S. aureus.…”
Section: Mediterranean Ormentioning
confidence: 92%
See 1 more Smart Citation
“…It is seen that propolis nanostructure containing solutions prevents proliferation of Staphylococcus aureus colonies effectively but not of Acinetobacter baumannii and Pseudomonas aeruginosa [15]. This proves that propolis extract containing nanostructure is effective on gram positive bacteria, Staphylococcus aureus [16][17][18][19]. …”
Section: Efficiency Of Samples On Gram-negative/-positive Bacterias Imentioning
confidence: 97%